Effect of the chronological age and sexual maturation on the time to exhaustion at maximal aerobic speed - Machado, F. A. (2007)
The purposes of this study were: a) to verify the effect of chronological age and sexual maturation on the time to exhaustion at VO(2)max (t(lim)) and; b) to examine the reproducibility of t(lim) in boys aged 10-15 years. Forty boys, divided into 4 groups, in accordance to the chronological age (G10-12 and G13-15) and sexual maturation (P1-P3 and P4-P5 levels for pubic hair), performed the following tests: 1) incremental test for determination of VO(2)max and; 2) all-out exercise bout performed at VO(2)max to determine the t(lim). There was no difference of t(lim) (sec) between G10-12 and G13-15 (181.5 +/- 96.3 vs. 199 105.5). While the two measures of t(lim) were moderately related (r = 0.78), t(lim) from the second test (226.6 +/- 96.1 s) was higher than that of the first (191.3 +/- 79.2 s). We can conclude that the t(lim) is not influenced by chronological age and sexual maturation. Besides, t(lim) presents a lower reproducibility in children and adolescents.